Identification of machine parameters in induction motor drive - Chong, Jason Nao Chen (2010)
Induction motors (IM) are the most widely used motors in industry because they are simple to build and rugged, reliable and have good self-starting capability. Due to their wide spread in industry, it is of great importance to devise a technique that can estimate different parameters of these motors which cannot be measured directly for different reasons. Planners models based on the original manufacturers’ information may not be accurate enough after a few years’ operation. In other situations, some simple man-made systems deviate from its designed behavior due to aging, wearing out, or change in a system parameter that was assumed to be static. Induction motor parameters change with temperature, frequency, and saturation. This project basically is based on identifying the machine parameters of induction motor drive by using Matlab software and introducing of Artificial Intelligent(AI) method through it. The set of differential equation was produced and used to model the system. To solve the set of differential equation, the Newton Raphson method have been used. By running the simulation using the Artificial Intelligent(AI) method that have been created, the machine parameters of the induction motor can be determine. As the result of the machine parameters been determined, the condition of the induction motor itself can be observe whether it still on under stable condition or running with lower performance